(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Although drugs are available for its treatment, administrations of those drugs have so many limitations and emergence of drug resistant strains of bacteria necessitate for the discovery of novel drugs. Plants are the best source of novel drugs and they are safe to use. Andrographis paniculata has been used in the Indian traditional medicine against tuberculosis, however, its efficacy was not tested and chemical molecules having the drug property are not identified. In the present investigation a total 140 chemical molecules derived from A. paniculata, 114 compounds collected from databases and 26 compounds determined through GC-MS analysis, were docked with three target proteins such as filamentous temperature sensitive protein Z (FtsZ), decaprenyl phosphoryl-beta D ribofuranose 2 epimerase (DprE1) and pantothenate kinase (PanK) and based on the lowest binding energy (≤-5kcal/mol) hit molecules were identified. Further hydrogen bond interaction and drug-likeness property analysis revealed that the compound β-sitosterol have inhibitory activity against FtsZ and DprE1. The compound 3,14 dideoxyandrographolide/andrograpanin showed least binding energy with PanK protein. The toxicity and drug-likeness property analysis indicated that among the hit molecules β-sitosterol is a promising lead molecule for the development of anti-tuberculosis drug. The results also substantiate the traditional use of this plant against tuberculosis.